Hierarchical Nickel–Cobalt‐Based Transition Metal Oxide Catalysts for the Electrochemical Conversion of Biomass into Valuable Chemicals. Issue 15 (12th July 2018) - Gao, Lifang; Bao, Yu; Gan, Shiyu; Sun, Zhonghui; Song, Zhongqian; Han, Dongxue; Li, Fenghua; Niu, Li
Abstract: The upgrading of biomass into sustainable and valuable fine chemicals is an alternative to the use of state‐of‐the‐art petrochemicals. The conversion of 5‐hydroxymethylfurfural (HMF) biomass derivative into 2, 5‐furandicarboxylic acid (FDCA) has been recognized as an economical and green approach to replace the current polyethylene terephthalate based plastic industry. However, this reaction mostly relies on noble‐metal‐based catalysts for the sluggish aerobic oxidation of alcohol groups. In this work, we report a series of hierarchical Ni−Co‐based transition metal oxide catalysts for HMF oxidation by electrocatalysis. Comprehensive material characterization and electrochemical evaluation have been performed. A 90 % FDCA yield, nearly 100 % Faradaic efficiency, and robust stability were achieved for NiCo2 O4 nanowires. As non‐precious‐metal catalysts, Ni−Co‐based transition metal oxides may open up new potential materials for highly efficient electrochemical biomass upgrading. Abstract : Biomass to building blocks : The electrochemical conversion of renewable biomass into value‐added chemicals and clean fuels by Ni−Co‐based transition metal oxide non‐precious‐metal catalysts is studied.